PHYSICAL FITNESS SURVEY OF BANYUMAS KARESIDENAN BASKETBALL REFEREES - Pratama, Raditya; Ruman (Four Son Scholarship, 2023)
The results of preliminary data observations of referees who have never conducted a physical fitness test (TKJI) at PERBASI Banyumas since 2015 until now. Based on the results of observations, it is important to conduct physical fitness research with the title